Development of Basic Concepts of Ethnographic Grounded Theory Research - Ghina Ulpah; Erni Haryanti; Tabah Sulistyono; Miftahul Huda; Nabihah Husna Razali (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
Grounded Theory Ethnography (GTE) research presents a cutting-edge methodology that combines the strengths of Grounded Theory (GT) and Ethnography. This approach opens the gates to understanding social and cultural phenomena in depth, generating solid theories based on empirical data. The primary goal of GTE is to develop or extend theory through systematic analysis of qualitative data. GTE researchers collect data through various ethnographic methods, such as participant observation, in-depth interviews, and document analysis. The data is then iteratively analyzed using GT techniques to identify emerging patterns, categories and concepts. GTE's strength lies in its ability to generate theories based on empirical data, not just assumptions. GTE allows researchers to capture the complexities and nuances of phenomena in their specific contexts, resulting in theories that are contextualized and culturally sensitive. This makes it useful for understanding and addressing complex social problems. GTE has been applied in various fields, such as education, sociology, anthropology, psychology, and public health. Its contribution to understanding various social and cultural phenomena, such as the immigrant experience, school culture, health practices and intergroup relations, is undeniable. GTE research paves the way for a deeper understanding of social and cultural realities. By combining the strengths of GT and Ethnography, GTE produces theories that are robust, relevant, and useful for solving various problems in society.